Comparison of the developmental and survival rates, adult longevity and fecundity of Helopeltis antonii Signoret (Hemiptera: Miridae) on different phenological stages of cashew - Srikumar, K.K.; Bhat, P.S. (Journal of Plantation Crops, 2011)
Among the several species of insect pests recorded on cashew in India, the Tea Mosquito Bug (Helopeltis antonii Signoret) is one of the serious pests. Nymphs and adults of H. antonii feed on cashew by sucking the sap from flushing shoots, panicles and immature fruits. The present study compared these food sources on the development, survival and oviposition of this species. The nymphal stages developed faster with enhanced survival rate when fed on fruits compared to those fed on flushing shoots or panicles. The whole developmental period of H.antonii was found to be 217.96 h on fruits, 225.23 h on panicle and 231.37 h on flushing shoots. The adults survived significantly longer when fed on fruits than fed on flushing shoots and panicles. The mean number of egg laid by H.antonii fed on fruits was 101.50 compared to 94.50 on panicles and 88.50 on flushing shoots. Adult TMB fed on fruits continued egg laying till 21st day after emergence while those fed on shoots and panicles laid eggs till 19th and 17th day, respectively.